Presentation of Novel Multiple Regression Model for Accounting Information Quality, Corporate Investment, and Moderating Role of Ownership Structure in Companies - Mahsa Amiran; Abdorreza Asadi; Maryam Oladi (Discrete Dynamics in Nature and Society)
The conflicts of interest between managers and shareholders force managers to make decisions that do not meet the interests of shareholders. One of these decisions is to invest less in the company’s operational activities. Increasing the information quality is one way to prevent that issue, allowing stakeholders to monitor investment decisions. The present study investigates the relation of accounting information quality, corporate investment, and ownership structure for Iranian firms, using panel data analysis from 2009 to 2018. We applied a multiple regression model to test the hypotheses. The results show that the quality of accounting information significantly affects the investment decision for the company’s main operations, so the first hypothesis of the research is confirmed. At the same time, there is no effect of capital structure on accounting information quality and firms’ investment decisions. Thus, the second hypothesis of the research failed to be confirmed.